Investigating Differentiated Learning Practices and their Influence on Multiple Domains of Early Childhood Development - Annisah Nurul Dzulaekha; Mohammad Syaifuddin; Mohamad Syahri (Jurnal Pendidikan Terapan, 2026)
Purpose : This study examines the systematic use of differentiated learning in early childhood classrooms at Hang Tuah Kindergarten, Tarakan, with a focus on its observed associations across six developmental domains moral-religious, physical-motor, cognitive, linguistic, socio-emotional, and artistic. It addresses the research gap in holistic analyses that move beyond single-domain evaluations. Methods: A qualitative methodology was used, incorporating classroom observations, semi-structured interviews with educators, and analysis of children's work artifacts. Data triangulation included instructional techniques, instructor perspectives, and developmental markers. Evidence was categorized into observed behaviors, instructor reflections, and documented outputs, with quality ratings assigned for systematic comparison. Findings: The study highlighted consistent differentiation in content, process, and product, with content adaptation deemed "adequate." Gains were observed in linguistic proficiency, collaboration, creativity, motor coordination, and cognitive sequencing. Teachers noted feasibility, alignment with readiness, and engagement from activity choice. Moderate progress was seen in moral-religious and socio-emotional domains, indicating a need for more focused scaffolding and long-term strategies. Research Implications: Findings indicate that differentiated learning significantly contributes to balanced child development, linking Tomlinson’s differentiation framework to Vygotsky’s sociocultural theory. The study suggests that differentiated strategies can enhance academic and social growth, prompting policymakers to consider institutional support for content adaptation. Originality: This research presents a qualitative account of differentiated learning across six developmental domains in Indonesian kindergartens, contributing a comprehensive framework that integrates teacher perceptions, classroom practices, and developmental artifacts, expanding upon previous studies that have predominantly focused on isolated domains.